Upaya Pencegahan Stunting Melalui Pemantauan Kesehatan, Edukasi, dan Pendampingan pada Ibu Hamil di Wilayah Bintaran dan Surokarsan Yogyakarta - Lusa Rochmawati; Kuswanti, Ina; Prabawati, Sulistyaningsih; Melina, Fitria; Wulandari, Setyo Retno (JOURNAL OF PHILANTHROPY: The Journal of Community Service, 2024)
Stunting is a condition where children under five fail to thrive due to chronic malnutrition and recurrent infections during the First 1000 Days of Life (HPK). Assistance for pregnant women can increase family understanding and be an effective strategy to empower families to increase readiness, especially in preventing stunting. The aim of community service activities is to carry out health monitoring and provide education to pregnant women regarding the results of examinations as an effort to prevent stunting through assisting pregnant women. The target of the activity is pregnant women in the Surokarsan and Bintaran areas, Wirogunan Village, Mergangsan Kemantren. The number of pregnant women recorded in September – December 2023 was 4 people. The method used is home visits by carrying out health monitoring and providing education through assistance to pregnant women. The results of activities in the form of health monitoring showed that all pregnant women were detected to be at high risk. The highest risk factors for pregnancy are anemia and pregnancy at too old an age (> 35 years). Education provided when assisting pregnant women about pregnancy anemia and high risk  pregnancies. After receiving education, pregnant women understand the importance of preventing anemia during pregnancy and are willing to consume blood supplement tablets regularly and fulfill balanced nutrition. Pregnant women understand that high-risk pregnancies are also a risk factor for stunting.